Comparison of one-year real-world outcomes between red (670 nm) subthreshold micropulse laser treatment and intravitreal aflibercept injection for treatment-naïve diabetic macular edema - Wataru Kikushima; Yukiko Furuhata; Taiyo Shijo; Mizuki Matsumoto; Yoichi Sakurada; Daphne Viel Tsuru; Kenji Kashiwagi (Photodiagnosis and Photodynamic Therapy)
Purpose: To evaluate the treatment outcomes of subthreshold micropulse laser (SMPL) with a wavelength of 670 nm (red) for treatment-naïve diabetic macular edema (DME). Methods: A retrospective observational study which included 42 eyes in 34 patients diagnosed with treatment-naïve DME was conducted. Twenty-one eyes underwent red SMPL and the other 21 eyes underwent intravitreal injection of aflibercept (IVA) as initial treatment and were followed up for 12 months. Best-corrected visual acuity (BCVA), central retinal thickness (CRT) on optical coherence tomography (OCT), vessel density (VD), and foveal avascular zone area on OCT angiography (OCTA) were measured and compared between the two groups. Results: In the red SMPL group, the mean BCVA slightly improved from 0.29 ± 0.28 at baseline to 0.22 ± 0.29 at 12 months (p = 0.18), while the mean CRT significantly decreased from 472 ± 200 µm at baseline to 320 ± 136 µm at 12 months (p = 0.003). At 12 months from baseline, the mean change in BCVA and CRT were similar between the red SMPL and IVA groups (p = 0.79 and p = 0.31, respectively). No significant change was detected in OCTA parameters except for VD at the nasal section in the red SMPL group. Conclusion: Red SMPL for treatment-naïve DME maintained BCVA and significantly reduced CRT at 12 months. These treatment outcomes were equivalent to IVA in real-world settings, which tend to be inferior to clinical trials.